Analisis Manajemen Fleet Pada Kegiatan Pengupasan Overburden Bulan Oktober 2019 di Pit 2 Dengan Penerapan Metode Quality Control Circle (QCC) Pada Optimalisasi Loss Time di Satuan Kerja Penambangan Swakelola PT. Bukit Asam Tbk, Sumatera Selatan. - Micco Syaputra; Yoszi Mingsi Anaperta (Departemen Teknik Pertambangan FT UNP, 2020)
Abstract. PT. Bukit Asam Tbk is a coal mining company in Indonesia and is a state-owned company (BUMN). PT. Bukit Asam Tbk applies an open mining system where the mining material is coal. The mining methods used are conventional mining and continuous mining methods. In October 2019 the Company Work Plan and Budget (RKAP) for overburden excavation at the Self-managed Mining Unit at pit 2 amounted to 1,200,000 Bcm, while the realization of the production of the Komatsu PC 3000E-6 Shovel Excavator in overburden stripping in the pit 2 months October 2019, namely 886,148,194 Bcm. And the realization of the production of Rigid Truck Belaz 75135 for overburden stripping at pit 2 in October 2019 was 561,839.582 Bcm.The low production of overburden stripping is due to the less than optimal effective working time due to the standby time for the Shovel Excavator Komatsu PC 3000E-6 and Rigid Truck Belaz 75135 due to the high dust loss time in the mining area as much as 301.99 hours. The purpose of this research is to optimize overburden production in mining by analyzing the suitability of mechanical devices using the match factor method and optimization of improvements using the quality control circle.Keywords : Coal Mining, Overburden, Loss Time, Dust, Shovel Excavator, Rigid Truck, Optimization, Match Factor, Quality Control Circle